2017
DOI: 10.1515/bot-2016-0056
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormones in red seaweeds: a technical review of methods for analysis and a consideration of genomic data

Abstract: Emerging studies suggest that seaweeds contain phytohormones; however, their chemical entities, biosynthetic pathways, signal transduction mechanisms, and physiological roles are poorly understood. Until recently, it was difficult to conduct comprehensive analysis of phytohormones in seaweeds because of the interfering effects of cellular constituents on fine quantification. In this review, we discuss the details of the latest method allowing simultaneous profiling of multiple phytohormones in red seaweeds, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 116 publications
1
22
0
Order By: Relevance
“…This is the case of Gibberella fujikuroi KAO, that produces GA 14 from ent-kaurenoic acid instead of GA 12 [104]. On the other hand, the algal groups Chlorophyta, Charophyta, and Phaeophyceae, have been reported to produce bioactive GAs in more than 30 species [106-108], while none has been found in Rhodophyta species [109]. Given that Chlorophyta and Charophyta lack clear CPS and KS orthologs [79], and Phaeophyceae algae are distantly related to Archaeplastid lineages [110], the most plausible explanation is that so far unidentified pathways for GA biosynthesis may have evolved independently in multiple lineages, in an extreme case of convergent evolution between kingdoms and domains.…”
Section: Evolution Of Gibberellin Metabolismmentioning
confidence: 99%
“…This is the case of Gibberella fujikuroi KAO, that produces GA 14 from ent-kaurenoic acid instead of GA 12 [104]. On the other hand, the algal groups Chlorophyta, Charophyta, and Phaeophyceae, have been reported to produce bioactive GAs in more than 30 species [106-108], while none has been found in Rhodophyta species [109]. Given that Chlorophyta and Charophyta lack clear CPS and KS orthologs [79], and Phaeophyceae algae are distantly related to Archaeplastid lineages [110], the most plausible explanation is that so far unidentified pathways for GA biosynthesis may have evolved independently in multiple lineages, in an extreme case of convergent evolution between kingdoms and domains.…”
Section: Evolution Of Gibberellin Metabolismmentioning
confidence: 99%
“…In addition, whether the phytohormones of land plants are shared with algae is controversial, especially given the distinct evolutionary relationship. Many of the signaling pathway components are not present in basal early-diverging lineages of the Streptophyta and/or other algal lineages (De Smet et al 2010, Lu andMori et al 2017) making it less likely that a phytohormone function could have been inherited from a common unicellular ancestor. Nonetheless, evidence for phytohormone function in unicellular algae is beginning to accumulate, such as the role of abscisic acid and auxins in regulation of growth in unicellular green algae and diatoms ( Kobayashi et al 1997, Yoshida et al 2004, Park et al 2013, Lu et al 2014, Amin et al 2015.…”
Section: Endogenous Signalingmentioning
confidence: 99%
“…Interactions have also been observed in land plants where pathogenic or symbiotic bacteria can influence the growth of a plant by manipulating its auxin homeostasis (Lambrecht et al 2000, Frugier et al 2008, Ludwig-Müller 2015. Therefore it is not certain if phytohormones are synthesized by algae themselves and metabolic auxotrophy may have evolved as a result of mutualism with microorganisms due to the aquatic environment (Kazamia et al 2016, Mori et al 2017.…”
Section: Endogenous Signalingmentioning
confidence: 99%
“…The presence and number of PGRs in algae and terrestrial plants differ according to the species or variety [12,22]. For example, Mori et al [41] reported the identification of auxins, cytokinins, and salicylic acid (SA), but not AG3 and jasmonates, in extracts of two red algae (Pyropia yezoensis and Bangia fuscopurpurea). Another study involving fourteen seaweeds in the Turkey coast reported the presence of five PGRs (t-zeatine (t-Z), IAA, GA3, ABA, and 6-benzyl amino purine (BAP) in two algae, namely Petalonia fascia (brown algae) and Caulerpa racemosa var.…”
Section: Discussionmentioning
confidence: 99%